Empowered Educators in Australia: How High-Performing Systems Shape Teaching Quality - Burns, Dion; McIntyre, Ann (Jossey-Bass, 2017)
BEST PRACTICES FROM AUSTRALIA'S HIGH-PERFORMING SCHOOL SYSTEMS Empowered Educators in Australia is one volume in a series that explores how high- performing educational systems from around the world achieve strong results. The anchor book, Empowered Educators: How High-Performing Systems Shape Teaching Quality Around the World, is written by Linda Darling-Hammond and colleagues, with contributions from the authors of this volume. The authors of Empowered Educators in Australia take an in-depth look at the policies and practices surrounding teaching quality in two different states: New South Wales (NSW) and Victoria. NSW offers significant support for government schools in areas such as staffing and teacher professional development. Victoria operates a highly devolved school system. Each provides a contrasting view of how federal and state policies combine to shape learning outcomes for students in Australia. The interplay between state and federal policy characterizes an intriguing "centralizing decentralization." Initiatives to create national curricular, teaching, and teacher education standards all sit in balanced tension with a movement towards greater devolution of authority to schools. Together the NSW and Victoria case studies provide insights into policies that can support high-quality teaching in a federal education system. Australia's current educational reforms place increasing emphasis on issues of teaching quality, reshaping teaching as a standards-based, evidence-informed profession, and one that seeks to foster collegiality and professional exchange. These reforms encompass many aspects of a system that supports teaching quality, and highlight: the way teachers are trained, how they are inducted into the teaching profession and supported with mentors, the professional learning they receive, how they are appraised on their work, and the career pathways for teachers.